ANALISIS PENGENDALIAN KUALITAS PROSES ASSEMBLY ENGINE B MENGGUNAKAN METODE SIX SIGMA DMAIC DI PT XYZ - Toby Fatwa Pratama (2023)
The research focused on the analysis of Type B engine quality control at PT XYZ, an automotive company. Type B machines have defect levels that are still above the company's tolerance limit, while Type A machines have met the tolerance limit. The purpose of the study was to minimize the number of defects that occurred in Type B machines. Six Sigma DMAIC method was used in this study. The "define" stage involves creating 9 critical requirements for quality (CTQ). The "measure" stage shows that oil leakage is the most dominant defect based on the Pareto Diagram, with an average Sigma Level of 4.826. In the "analyze" stage, Fault Tree Analysis (FTA) and Failure Mode and Effects Analysis (FMEA) are carried out to identify dominant factors that affect defects, such as People, Machines, Materials, and Methods. Environmental factors do not have a significant influence. The "improve" stage produces 10 proposed improvements, which are then simulated in the "control" stage using Monte Carlo simulation to calculate Sigma Levels. After simulation, the Sigma Level performance was 4.709, a decrease from the previous year of 0.110. Simulations were also carried out with 3 success scenarios to reduce dominant defects by 50%, 75%, and 100%. The Sigma Level value increases in the second scenario to 4.833, and in the third scenario to 4.888. In 2023, the company suffered a loss of Rp. 13,000,000, - due to a leaking oil defect. However, implementation is expected to reduce the risk of oil defects leaking to zero, so that losses can be avoided.